2013
DOI: 10.1186/1471-2164-14-558
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of non-coding RNAs in the antibiotic-producing Streptomyces bacteria

Abstract: BackgroundNon-coding RNAs (ncRNAs) are key regulatory elements that control a wide range of cellular processes in all bacteria in which they have been studied. Taking advantage of recent technological innovations, we set out to fully explore the ncRNA potential of the multicellular, antibiotic-producing Streptomyces bacteria.ResultsUsing a comparative RNA sequencing analysis of three divergent model streptomycetes (S. coelicolor, S. avermitilis and S. venezuelae), we discovered hundreds of novel cis-antisense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 97 publications
3
71
0
Order By: Relevance
“…Such effects have been suggested for antibiotic production in Streptomyces, with many ncRNAs being specified within antibiotic biosynthesis clusters (73). Taking into account available data about ncRNAs in S. coelicolor (73)(74)(75), we identified two inserts in intergenic small RNA (sRNA) regions (scr3437 and scr3580) that influenced RED production.…”
Section: Discussionmentioning
confidence: 99%
“…Such effects have been suggested for antibiotic production in Streptomyces, with many ncRNAs being specified within antibiotic biosynthesis clusters (73). Taking into account available data about ncRNAs in S. coelicolor (73)(74)(75), we identified two inserts in intergenic small RNA (sRNA) regions (scr3437 and scr3580) that influenced RED production.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were frozen at Ϫ80°C for 3 to 6 days. Total RNA was extracted by mechanical disruption, and coextracted DNA was digested using Turbo DNase (Ambion), as previously described by Moody et al (22). Total RNA was quantified using a NanoDrop ND-1000, and RNA integrity was confirmed by size fractionating 2 g of total RNA on an agarose gel.…”
Section: Methodsmentioning
confidence: 99%
“…1A). Analysis of data from previously published RNA-sequencing (RNA-seq) experiments (32) suggested that each of rnj, dapA, and thyX was expressed from a distinct promoter but also shared low-level readthrough transcription, particularly between dapA and rnj (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…1B). The investigation of available RNA-seq data (32) suggested that while these three genes do indeed appear to be cotranscribed in S. venezuelae, there exists an additional encoding genes (thyX, dapA, and rnj) is shown a graph of relative transcript levels throughout this region, as determined using RNA-seq data from RNA samples representing all stages of S. venezuelae growth (RNA was harvested at three distinct growth stages, vegetative, fragmentation, and sporulation, and was combined prior to sequencing). (B) Genetic organization of the RNase III-encoding rnc region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation